Influence of cultivation conditions on growth, sporulation rate and δ-endotoxin synthesis of Bacillus thuringiensis MPK13 - Mohd. Masri, Mohamed Mazmira (2013)
The influence of cultivation conditions on growth of Bt MPK13, sporulation rate,δ- endotoxin synthesis and its toxicity was the focus of this study. The Cry+ strain of Bt MPK13 with consistent ability in δ-endotoxin synthesis was selected by repeated isolation with polymerase chain reaction analysis and δ-endotoxin detection. The effect of monosaccharides (glucose, fructose and galactose) and disaccharides (sucrose, lactose and maltose) on growth of Bt MPK13, sporulation and δ-endotoxin synthesis was carried out using shake flask culture. The data generated was also used to find the relationship between intracellular and extracellular total carbon (TC), total nitrogen (TN) and C/N ratio on growth of Bt MPK13, sporulation and δ-endotoxin synthesis. The effect of dissolved oxygen tension (DOT) control strategies and also the influence of different modes of bioreactor operation (batch, fed-batch and continuous) on the cultivation performance of Bt MPK 13 was investigated using 5 L stirred tank bioreactor. The existence of δ-endotoxin was detected using SDS-PAGE analysis and the toxicity of δ-endotoxin synthesized during different modes of bioreactor operation was carried out against early instars of bagworms, Metisa plana. The selected Cry+ strain of Bt MPK13 was preserved as the stock culture in freeze dried form. The use of Cry+ strain of Bt MPK13 as the stock culture resulted to a consistent 8-endotoxin synthesis in repeated experiments. During cultivation, sucrose, fructose,galactose, lactose and maltose were able to support growth of Bt MPK13, but failed to enhance high percentage of sporulation and the existence of δ-endotoxin was not detected. The synthesis of δ-endotoxin was only detected in cultivation using glucose as the carbon source. Mixture of glucose with other sugars also recorded high cell growth (>1.0 x 1012 cfu/mL) with high percentage of sporulation ( 35%) however, the synthesis of δ-endotoxin was only detected when glucose concentration used in a mixture was higher than 8 g/L, indicating that high glucose concentration (> 8 g/L) must be present in the culture to trigger δ-endotoxin formation.. The highest initial and final intracellular TC and TN were also recorded in cultivation using glucose as the sole carbon source which corresponded well to high cell growth, high percentage of sporulation and δ-endotoxin synthesis. High DOT level (80% saturation) during active growth phase of Bt MPK13 was compulsory for 8-endotoxin synthesis in batch cultivation using glucose (8 g/L) as a carbon source. Enhanced percentage of sporulation (up to 61%) with early 8-endotoxin synthesis (8 h of cultivation) was obtained in cultivation where the DOT was controlled at 80% saturation during active growth and then switched to 60% or 40% saturation at mid-exponential growth phase (after 6 h). The application of this optimal DOT control strategy without affecting the cell growth could also be used to enhance the percentage of sporulation (> 45%) and 8-endotoxin synthesis in fed-batch cultivation. The highest viable cell count (1.5 x 1012 cfu/mL) and spore count (7.1 x 1011 spore/mL) with the existence δ-endotoxin was obtained in fed-batch cultivation with constant feeding of 2 L, 8 g/L glucose at 6 h of cultivation, and optimal DOT control strategy was applied. Compared to batch cultivation, fed-batch without DOT control strategy able to increase cell count (24% increment), however spore count was greatly decreased (50% decrement). Feeding of glucose at stationary phase and intermittent feeding resulted to non-existence of δ-endotoxin. In continuous cultivation, the highest cell (5.8 x 1014 cfu/L.h) and spore (1.6 x 1013 spore/L.h) productivities were obtained at the dilution rate (D) of 0.39 h-1 and 0.05 h-1, respectively. Although the steady-state viable cell concentration (1.7 x 1012 cfu/mL) was substantially higher than those obtained in batch cultivation, more than 50% decrement in spore count was recorded. It is important to note that 8-endotoxin synthesis was not detected in all D tested in continuous cultivat ion,indicating that this cultivation technique is not suitable for Bt production. The culture with the existence of δ-endotoxin recorded 100% mortality towards bagworms (M. plana) at 14 DAT which was related to oil palm defoliation, suggesting that Bt MPK13 has potential to be used as industrial biopesticide. The proposed optimal cultivation conditions may be used in the development of large scale cultivation of Bt MPK13 for subsequent use as biopesticides in oil palm plantation.